NMD3 regulates both mRNA and rRNA nuclear export in African trypanosomes via an XPOI-linked pathway. Issue 9 (14th April 2015) - Bühlmann, Melanie; Walrad, Pegine; Rico, Eva; Ivens, Alasdair; Capewell, Paul; Naguleswaran, Arunasalam; Roditi, Isabel; Matthews, Keith R.
Abstract: Trypanosomes mostly regulate gene expression through post-transcriptional mechanisms, particularly mRNA stability. However, much mRNA degradation is cytoplasmic such that mRNA nuclear export must represent an important level of regulation. Ribosomal RNAs must also be exported from the nucleus and the trypanosome orthologue of NMD3 has been confirmed to be involved in rRNA processing and export, matching its function in other organisms. Surprisingly, we found that Tb NMD3 depletion also generates mRNA accumulation of procyclin-associated genes (PAGs), these being co-transcribed by RNA polymerase I with the procyclin surface antigen genes expressed on trypanosome insect forms. By whole transcriptome RNA-seq analysis of Tb NMD3-depleted cells we confirm the regulation of the PAG transcripts by Tb NMD3 and using reporter constructs reveal that PAG1 regulation is mediated by its 5′UTR. Dissection of the mechanism of regulation demonstrates that it is not dependent upon translational inhibition mediated by Tb NMD3 depletion nor enhanced transcription. However, depletion of the nuclear export factors XPO1 or MEX67 recapitulates the effects of Tb NMD3 depletion on PAG mRNAs and mRNAs accumulated in the nucleus of Tb NMD3-depleted cells. These results invoke a novel RNA regulatory mechanism involving the NMD3-dependent nuclear export of mRNA cargos, suggesting a shared platform for mRNA and rRNA export.